PENGARUH CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN TOYOTA KIJANG INNOVA DIESEL REBORN DI SURABAYA - Listiono, Daniel Onesimus (Seminar Nasional Ilmu Terapan, 2024)
Globalization has resulted in extremely quick changes across a number of industries, including the automotive, technological, and health sectors. Changes in Indonesian automotive trends provide insight into this development. Even at distant locations, everyone must be able to work swiftly and efficiently. People need a way to get from one place to another quickly, whether it is nearby or far away. Humans require transportation as a tool in order to travel great distances swiftly. The purpose of this study is to ascertain how consumer decisions about the Toyota Kijang Innova Diesel Reborn in Surabaya are influenced by brand image and product quality. Primary data from questionnaires was employed in this quantitative research design. The study population included individuals who owned Kijang Innova diesel rebirth automobiles in Surabaya throughout the research period. A sample of 97 respondents was employed for data analysis, and SPSS data processing was utilized for data processing. As a result, it is known that 1) Brand Image has a positive influence on purchasing decisions. It can be said that the Toyota company's efforts in building a brand image can be said to be successful because it succeeded in creating an emotional relationship. This shows that a strong emotional relationship can encourage consumers to make purchasing decisions. 2) Product quality has a positive effect on purchasing decisions. The results of this research found that serviceability (speed, convenience and access) is the indicator of product quality that is most felt by consumers. This factor is very important and supportive for consumers, therefore Toyota is thinking about this by building many car showrooms along with service services in various regions throughout Indonesia so that the prices and goods offered to consumers are very cheap and fast.